Novel Substituted-dene-2-(-1,3-Diphenylallylidene) Hydrazine: Design, Synthesis, and in vitro Microbial Assessment - Parthiban, P.; Saravanakumar, A.; Mohanraj, S.; Kavinkumar, M. C.; Sangeetha, S.; Loganathan, M.; Vivekanandan, N.; Abbinanthan, M.; Bharat, P.; Santhosh, M.; Muthuraj, M.; Lakshminarayanan, B. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The production of a variety of chalcones (1-Aryl/Alkyl amino substituted-dene-2- (-1,3-diphenylallylidene) hydrazine (ABSa-e) was brought about as a result of the condensation of hydrazide compound and Aryl/Alkyl substituted aldehyde/ ketone in ethanol as a solvent with the help of two drops of conc. hydrochloric acid as a catalyst followed by neutralization. All synthesized derivatives were identified with different spectroscopic techniques and biologically evaluated by microorganisms. Materials and Methods: The in vitro antibacterial and antifungal activity of all synthesised compounds was evaluated. In the microbial studies, the five strains of selected bacteria and two strains of fungi have been used to evaluate the synthesized compounds, DMSO used as the solvent, and amoxicillin and griseofulvin used as control drugs. Results and Conclusion: Derivatives exhibited the highest potency (17mm, 18mm, 16mm, 18mm, 15mm) (MIC) with the electron donating groups (CH3) in position 4 of the phenyl ring (ABSc). On the other hand, the withdrawing group (NO2, Cl) of compounds ABSb & ABSe showed the most negligible potency against selected microorganisms. The unsubstituted phenyl ring (ABSa) showed moderate activity (17mm, 15mm, 15mm, 16mm, 14mm) at 100 μg/mL. The oxygen-containing furan compound ABSd proved as the second-highest potency (16mm, 17mm, 15mm, 17mm, 14mm) of this series. All of the results pointed to compound ABSc as a potential antibacterial lead molecule, and efforts are currently being made to increase the potency of amino chalcone derivatives.
Keywords: Chalcone; Aldehyde; Antibacterial; Antifungal; Potency